2023
DOI: 10.1007/s00737-023-01327-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of digital psychological interventions in reducing perinatal depression: a systematic review of meta-analyses

Abstract: Digital psychological interventions have been widely used clinically in recent years, but the methodological quality and quality of evidence of related studies are unclear, thus interfering with the translation of practice outcomes and the application of clinical decisions. We searched for meta-analyses of randomized controlled trials in the PubMed, Web of Science, Embase, Cochrane Library, JBI Database, CINAHL, and PsycINFO databases as well as some databases containing gray literature up to 27 April 2022 usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Partners were taught to provide support and to prevent conflict or distress in postnatal subjects undertaking CBT sessions [42] . Chen C et al [43] reported that both mindfulness therapy and CBT interventions significantly decreased depressive symptoms in the intervention group compared with those in the control group. However, it remains inconclusive whether iCBT is more successful than other therapies in addressing perinatal depression compared to anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Partners were taught to provide support and to prevent conflict or distress in postnatal subjects undertaking CBT sessions [42] . Chen C et al [43] reported that both mindfulness therapy and CBT interventions significantly decreased depressive symptoms in the intervention group compared with those in the control group. However, it remains inconclusive whether iCBT is more successful than other therapies in addressing perinatal depression compared to anxiety.…”
Section: Discussionmentioning
confidence: 99%